Odpowiedzi

Najlepsza Odpowiedź!
2010-02-02T23:42:52+01:00

4(2x + 3)-2(4y -1) = 30
5x + 1/3 - y-3/4 =3 /*3

8x+12-8y+2=30
15x+1-3y-9/4=9/*4

8x=16+8y
60x+4-12y-9=36

8x=16+8y/:8
60x+4-36-9=12y

x=2+y
12y=60(2+y)-41

x=2+y
12y=120+60y-41

x=2+y
-48y=79 /:(-48)

x=2+(-79/48)
y=-79/48

x=17/48
y=-79/48

22 3 22
2010-02-02T23:44:40+01:00
4(2x + 3)-2(4y -1) = 30
5x + 1/3 - y-3/4 =3

8x + 12 -8y +2 = 30
-y = 3 - 5x - 1/3 + 3/4 /*(-1)

8x + 12 - 8 (5x - 41/12) + 2 = 30
y = 5x - 41/12

8x -40x = 30 - 12 - 82/3 /: (-32)
y = 5x - 41/12

x = 7/24
y = 5*7/24 - 41/12

x = 7/24
y = -47/24
11 2 11